Effect of Environmental Parameters To Catch Gill Net in Korong Manggopoh Dalam the District Ulakan Tapakis Ulakan village of Padang Pariaman district of West Sumatra Province - Hasbi As Sidiq; Usman M Tang; T. Ersti Yulika Sari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Research on the Effect of Environmental Parameters To Catch Gill Net inKorong Manggopoh In the District Ulakan Tapakis Ulakan Nagari PadangPariaman in West Sumatra province did on March 16 to 29 by 2015, aims todetermine the state of operation of the aquatic environment gill net fishing gearsuch as depth, brightness , flow velocity, temperature, salinity, pH, and species offish caught in waters Korong Manggopoh in. The method used in this research is asurvey method that is by measuring the direct observation of environmentalparameters and operation of a gill net fishing gear research location. The datacollected in this study are: demographics, topography, depth, brightness,temperature, salinity, current velocity, and pH. The catch and the measurement ofthese parameters are collected and tabulated into a table and analyzeddescriptively.The observation of environmental parameters during penelititan is thetemperature range 29 0C - 30 0C, salinity ranged between 23 ‰ - 25 ‰, Flowranges from 0.16 m / s - 0.25 m / s, Brightness ranges from 10 m - 16 m , depthrange between 12.2 to 15.9 m and pH (acidity) ranged between 7- 9.2.Keywords: Gill net, gill net operating area